Exploring Al-Quran proficiency among indigenous communities in Malaysia: an analysis on mastery levels across diverse tribal groups - Ismail, Halim; Abdul Razak, Fahmi Zaidi; Mustapha, Ramlan; Mokhtar, Nazatul Akmar; Abdul Rahman, Asmadi; Sh Othman, Sh Mohd Firdaus (Academic Inspired Network, 2023)
This study examines the proficiency levels of Al-Quran recitation among indigenous communities in Malaysia, specifically focusing on diverse tribal groups. The mastery of Al-Quran recitation is crucial for comprehensive understanding and knowledge of its teachings. However, there is a lack of information on the mastery levels of indigenous populations, particularly among specific tribes. This study aims to address this research gap by assessing the level of Al-Quran recitation mastery within specific indigenous tribes. The study follows a structured approach, starting with an introduction that emphasizes the importance of indigenous peoples' knowledge and the significance of Quranic recitation mastery. A comprehensive literature review explores previous studies on the importance of religious knowledge and its dissemination among indigenous communities. The methodology section outlines the research design and data collection methods used to assess mastery levels among specific tribes. The findings of the data analysis are presented, including the observed proficiency levels within each tribe. The study reveals the distribution of respondents across various tribes and highlights the progress of respondents at different stages of Quranic mastery. The discussion section provides an interpretation of the results, implications for religious authorities, and identifies potential areas for further research. Overall, this study contributes to a better understanding of the Al-Quran proficiency among indigenous communities, enabling religious authorities to tailor interventions and approaches to address the unique needs of these tribes.